2015
DOI: 10.1038/srep13231
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Physiologically Responsive Low-Density Lipoprotein Receptor-Mediated Endocytosis in Genetically Deficient Induced Pluripotent Stem Cells

Abstract: Acquiring sufficient amounts of high-quality cells remains an impediment to cell-based therapies. Induced pluripotent stem cells (iPSC) may be an unparalleled source, but autologous iPSC likely retain deficiencies requiring correction. We present a strategy for restoring physiological function in genetically deficient iPSC utilizing the low-density lipoprotein receptor (LDLR) deficiency Familial Hypercholesterolemia (FH) as our model. FH fibroblasts were reprogrammed into iPSC using synthetic modified mRNA. FH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…Each experimental condition was quantified for length density (i.e., a ratio of the total EC length to the 3D scan volume; Figure 20B) as well as the Adipose SVF is a heterogeneous cell population that contains EC, perivascular cells, macrophage, fibroblasts and stem cells 9,369,400 . This endogenous heterogeneity is likely what imbues the cellular system with the specific capacity to form functional microvasculatures in vivo 1,9,370 . In prior efforts, we leveraged this functionality to support the engraftment of hepatic parenchymal cells 1,9 .…”
Section: 001) Ns = Not Significant Results Shown As Mean ± Semmentioning
confidence: 99%
See 4 more Smart Citations
“…Each experimental condition was quantified for length density (i.e., a ratio of the total EC length to the 3D scan volume; Figure 20B) as well as the Adipose SVF is a heterogeneous cell population that contains EC, perivascular cells, macrophage, fibroblasts and stem cells 9,369,400 . This endogenous heterogeneity is likely what imbues the cellular system with the specific capacity to form functional microvasculatures in vivo 1,9,370 . In prior efforts, we leveraged this functionality to support the engraftment of hepatic parenchymal cells 1,9 .…”
Section: 001) Ns = Not Significant Results Shown As Mean ± Semmentioning
confidence: 99%
“…This endogenous heterogeneity is likely what imbues the cellular system with the specific capacity to form functional microvasculatures in vivo 1,9,370 . In prior efforts, we leveraged this functionality to support the engraftment of hepatic parenchymal cells 1,9 . Koh and colleagues demonstrated that the formation of vascular networks by mouse SVF (mSVF) depended on the presence of EC and is VEGF-dependent 299 .…”
Section: 001) Ns = Not Significant Results Shown As Mean ± Semmentioning
confidence: 99%
See 3 more Smart Citations